Rotational spectroscopy of diatomic molecules - Brown, John M. (Cambridge molecular science series., 2003)
Written to be the definitive text on the rotational spectroscopy of diatomic molecules, this book develops the theory behind the energy levels of diatomic molecules and then summarises the many experimental methods used to study their spectra in the gaseous state.